2014
DOI: 10.1186/1471-2415-14-104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of retinopathy on the achromatic and chromatic vision of patients with type 2 diabetes

Abstract: BackgroundLuminance contrast sensitivity and colour vision are considered to have great predictive value in the evaluation of type 2 diabetic retinopathy. However, these two visual characteristics have seldom been investigated in the same group of patients. In the present study we measured contrast sensitivity and colour vision in a group of patients with type 2 diabetes and correlated the results with estimates of common metabolic markers for the disease. A subgroup of the patients had no clinical signs of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
(60 reference statements)
5
27
2
Order By: Relevance
“…Previous studies by Andrade et al, Feitosa-Santana C et al, and Sun TS and Zhang MN showed that ICV could develop in the early stage of T2DM but did not specify the minimal period for the development of color vision deficiency [2–4]. The results of this study suggest that the risk of DM increases for each additional year after the onset of T2DM.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies by Andrade et al, Feitosa-Santana C et al, and Sun TS and Zhang MN showed that ICV could develop in the early stage of T2DM but did not specify the minimal period for the development of color vision deficiency [2–4]. The results of this study suggest that the risk of DM increases for each additional year after the onset of T2DM.…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, patients with type 2 DM without diabetic retinopathy presented altered CSV only for high spatial frequencies (12 and 18 cpd). These results support previous findings, where loss of contrast sensitivity in type 2 diabetics who do not have diabetic retinopathy was hardly observed [5,14,16]. However, other researchers have found changes affecting CSV in all frequencies in patients with DM2 and no retinopathy [15,17].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the evaluation of CSV in different spatial frequencies is of great importance in these patients. It appears that, in the presence of clinical diabetic retinopathy, a decrease in contrast sensitivity is present [5,14], which may be independent of the visual acuity affectation [5,15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Early retinal changes may manifest in subtly altered visual functions such as color discrimination, which may appear before any visual acuity deterioration or clinically apparent retinopathy (Andrade et al, 2014). Patients can maintain good visual acuity for many years and are commonly unaware of any retinal damage or deterioration in vision (Andrade et al, 2014).…”
Section: Microperimetry and Diabetic Retinopathymentioning
confidence: 99%